1986
DOI: 10.1037/h0085636
|View full text |Cite
|
Sign up to set email alerts
|

The "inner voice" and suicide.

Abstract: The "voice" refers to an internal system of hostile thoughts and attitudes, antithetical to the self and cynical toward others. It reaches its most dangerous and life-threatening expression in suicidal acting-out behavior.Preliminary studies indicate that this partly conscious thought process is at the root of much depressive behavior and lowered self-esteem and that there is powerful negative affect accompanying the inner voice. The voice is described as a core defense that originated in family interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Might the inner voice be the core of a negative self-concept which develops during the most severe stage of the eating disorder as was suggested by Firestone (1986)? Could these negative inner voices be related to low self-esteem and high self-criticism, factors which have previously been found to be key in the onset and development of eating disorders (Dunkley, Blankstein, Masheb, & Grilo, 2006;Dunkley & Grilo, 2007;Dunkley, Masheb, & Grilo, 2010;Fennig et al, 2008)?…”
Section: Critical Inner Voicesmentioning
confidence: 92%
See 2 more Smart Citations
“…Might the inner voice be the core of a negative self-concept which develops during the most severe stage of the eating disorder as was suggested by Firestone (1986)? Could these negative inner voices be related to low self-esteem and high self-criticism, factors which have previously been found to be key in the onset and development of eating disorders (Dunkley, Blankstein, Masheb, & Grilo, 2006;Dunkley & Grilo, 2007;Dunkley, Masheb, & Grilo, 2010;Fennig et al, 2008)?…”
Section: Critical Inner Voicesmentioning
confidence: 92%
“…Hence, the term voice may deter many participants, as they may be afraid of appearing to have a psychotic illness. With reference to Firestone's (1986) definition of inner voices the word voice might be replaced with thoughts which you experience as a voice. Prospective research should make clear when having negative critical thoughts are heard as critical voices.…”
Section: Strengths Limitations and Future Outlookmentioning
confidence: 98%
See 1 more Smart Citation
“…Firestone (1988) described how such a usually dormant but always vigilant inner voice manifests itself by a series of "thoughts and attitudes, antithetical toward self and cynical towards others" (p. 33). It frequently pushes towards suicide (Firestone, 1986). It can make a client forget an appointment, feel ridiculous for seeking therapy, or too drowsy to connect and share.…”
Section: Person-centered and Experiential Psychotherapies 81mentioning
confidence: 98%
“…Research by Firestone (1996, 1998) and Firestone (1986Firestone ( , 1990) on family factors and suicide outcomes lends additional support to the importance of family communication interaction and suicide risk. Although they take a psychodynamic approach to the study of suicide, Firestone and Firestone's (1998) research findings strongly suggested that relationships with significant primary figures, especially parents, which are intrusive or rejecting in the face of failure are likely to be internalized and can increase the risk of suicide in later life.…”
Section: Family Dynamic Approaches To Understanding Suicidementioning
confidence: 98%